PERENCANAAN PERLENGKAPAN JALAN DENGAN MENGADOPSI PRINSIP-PRINSIP KESELAMATAN DAN US MUTCD - Muhammad Ahlan (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
Road equipment includes, but not limited to sign, mark, safety facility, and the other road user facilities. The road equipment design procedure in Indonesia is regulated through the standard, but the detail is allowed to be set using engineering judgment. US manual on uniform traffic control devices (US MUTCD) provides the detail that might be used, together with the safety principle, in the detail of road equipment design procedure in Indonesia. The objective of this study is to conclude the principle of safety and principle from the US MUTCD that might be used in the detail of road equipment design in Indonesia, especially for the medium-premiers collector road. The survey was performed at a segment of collector road in Province of Aceh, Indonesia. The road geometry, road users, adjacent hazard and surrounding people's activities were monitored in the survey. The drawing of the road was used as the secondary data as well. The result of this study is the recommendation on designing the feasibility and the number of signs, the distance between signs, and the pedestrian facility. Keywords—Road equipment, premier collector road, sign